Frequency and risk factors of sleep problems in Egyptian patients with multiple sclerosis - Khedr, Eman M.; Ahmed, Gellan K.; Hassan, Shady Safwat; Foly, Mohamed Nageh; Attia, Motez Mahmoud; Karim, Ahmed A.; Haridy, Nourelhoda A. (Frontiers in Neurology, 2025)
BackgroundSleep problems impact over 65% of patients with multiple sclerosis (MS), a prevalence significantly greater than that observed in the general population. This study aimed to assess the frequency and risk-associated factors of sleep problems in a large MS cohort and evaluate their impact on quality of life (QoL).MethodsThe study included 103 participants with MS across different disease stages and 62 healthy controls. Assessment tools included the Expanded Disability Status Scale (EDSS), Pittsburgh Sleep Quality Index (PSQI), depression and fatigue scales, 9-Hole Peg Test, 25-foot walk test, cognitive function assessments, and QoL measures.ResultsSleep problems were significantly more frequent in MS patients (68.9%) than in controls (30.6%). PSQI scores showed positive correlations with the number of MS relapses across the course of disease duration, walking impairment, fatigue and depression scores. Sleep problems were determined to adversely affect various domains of quality of life.ConclusionOur findings demonstrate that sleep problems are remarkably common among patients with MS. Patients experiencing poor sleep quality are typically associated with higher levels of fatigue, depression, greater difficulty with mobility, and more frequent disease relapses. These sleep problems significantly impaired the overall QoL in MS patients. A multidisciplinary approach is therefore essential for managing sleep disorders in MS.